Climate Change Adaptation Measures in Vietnam : Development and Implementation /: Development and Implementation. (2015) - Schmidt-Thomé, Philipp; Nguyễn, Thị Hà; Phạm, Thành Long; Jarva, Jaana; Nuottimäki, Kristiina
No abstract available